Candidates for a possible third-generation gravitational wave detector: comparison of ring-Sagnac and sloshing-Sagnac speedmeter interferometers. (20th December 2016) - Huttner, S H; Danilishin, S L; Barr, B W; Bell, A S; Gräf, C; Hennig, J S; Hild, S; Houston, E A; Leavey, S S; Pascucci, D; Sorazu, B; Spencer, A P; et al.
Abstract: Speedmeters are known to be quantum non-demolition devices and, by potentially providing sensitivity beyond the standard quantum limit, become interesting for third generation gravitational wave detectors. Here we introduce a new configuration, the sloshing-Sagnac interferometer, and compare it to the more established ring-Sagnac interferometer. The sloshing-Sagnac interferometer is designed to provide improved quantum noise limited sensitivity and lower coating thermal noise than standard position meter interferometers employed in current gravitational wave detectors. We compare the quantum noise limited sensitivity of the ring-Sagnac and the sloshing-Sagnac interferometers, in the frequency range, from 5 Hz to 100 Hz, where they provide the greatest potential benefit. We evaluate the improvement in terms of the unweighted noise reduction below the standard quantum limit, and by finding the range up to which binary black hole inspirals may be observed. The sloshing-Sagnac was found to give approximately similar or better sensitivity than the ring-Sagnac in all cases. We also show that by eliminating the requirement for maximally-reflecting cavity end mirrors with correspondingly-thick multi-layer coatings, coating noise can be reduced by a factor of approximately 2.2 compared to conventional interferometers.